Inconsistent behavior in online consumer reviews: The effects of hotel attribute ratings on location - Mellinas, Juan Pedro; Nicolau, Juan L.; Park, Sangwon (Tourism Management, 2019)
The purpose of this article is to analyze the effects of hotel attribute ratings on location. This analysis is highly pertinent given the prevailing use of reviews and their potential interdependence. Within the framework of prospect theory, the results show that: i) the assessment of location is influenced by the evaluation of other hotel attributes; ii) this influence is asymmetric, in line with the loss aversion phenomenon (the consumer punishes the hotel more harshly for dissatisfaction than praises it lavishly for satisfaction); and iii) the effect of a change in the evaluations of other hotel attributes on the assessment of location presents a pattern that reverses the diminishing sensitivity property. Relevant research and managerial implications are outlined.
Keywords: diminishing sensitivity; location; loss aversion; prospect theory; ratings; reviews; JCR; Scopus